The Influence of Brises and Curtains on the Energy Efficiency of Office Buildings - Vidmar, Rangel Girardelo; Cunha, Eduardo Grala da; Silva, Thaísa Leal da (Technical and Scientific Journal Green Cities, 2024)
The construction sector is responsible for a significant portion of energy consumption and greenhouse gas emissions. In this sense, it is extremely important that initiatives are developed to reduce the energy consumption of buildings, contributing to the sustainability of these buildings. Among the alternatives for reducing energy consumption is the possibility of inserting shading devices into building windows.  In this context, this work aims to analyze the influence of the use of shading devices on windows of an office building model geographically located in Passo Fundo - RS. To this end, 24 computer simulations were carried out using the Energy Plus software in a model of an office building considering its windows without any shading device and, subsequently, with the installation of two different types of sun shades and curtains that act according to the internal temperature of the building. environment and with a pre-defined agenda. Single and double glazing were also tested. The results revealed positive influences of shading devices in the office building, reducing electrical energy consumption by up to 4.64% in relation to the reference case. Therefore, the use of sunshades and curtains can help reduce energy consumption in the building, maintaining the thermal comfort of the environment.
Keywords: Thermal performance; Solar breezes; Computer simulation